PERANCANGAN SISTEM INFORMASI PERSEDIAAN BARANG BERBASIS WEB DENGAN ANALISA PIECES - Jelman Nasri; Indra Hiswara; Rizki Kosasih (JRIS : Jurnal Rekayasa Informasi Swadharma, 2022)
Information is an element that links management functions which consist of planning, operating, and controlling the company. Without information a company will not be able to carry out the company's operational activities properly. One of the information needed is inventory information. The warehouse department must record every time a transaction occurs, namely incoming goods, outgoing goods and stock of goods. This requires accuracy from the warehouse, so that in every report there is no error, this will be a problem for the company. This company needs a web-based inventory system in order to help the process of inventory better. The research method used is field research, with data collection techniques through observation and interviews. From the current system analysis is carried out using the PIECES method (Performance, Information, Economy, Control, Efficiency, and Services). The purpose of this study is to design a system that is able to produce accurate inventory data information and can provide real time stock data